HRM Transition in Indonesian Companies: Linear and Non Linear Approaches - Thoha, N.; Bickley, Maureen; Whiteley, Alma (World Business Institute, 2006)
The paper reports on a study of human resource management practices in seven large Indonesian Companies. Current practices reported by company staff were considered against a conceptual framework representing the stages of Personnel Administration, Human Resource Management, and Strategic Human Resource Management. Results provide clear evidence of practices in each stage occurring simultaneously. The data in one company, reported here, challenges the more usual notion of an integrated and linear HRM system and is replaced by a combination of linear and non- linear elements. There was with clear evidence of transition and adaptation.